Carbon footprint of lentil in old Brahmaputra floodplain soil - Haq, ME; Kader, MA; Farhan, S (Progressive Agriculture, 2016)
Crop production has contributed significantly to global carbon footprint (CF). Characterizing the carbon footprint of agricultural production offers key information for achieving low carbon agriculture. Bangladesh has struggled for long and worked hard for increasing food production capacity for its large growing population. It is necessary to choose the crops and management practices which have low CF to maintain a win-win situation between food production and greenhouse gas (GHG) emissions. However, the CF of Bangladeshs crop production has not yet been assessed. Therefore, this study was conducted to estimate the CF of lentil as one of the major legumes cultivated in Bangladesh. The crop was cultivated at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU) Farm, Mymensingh i.e. Agro-ecological zone (AEZ 9) during November, 2013 to April, 2014 by following standard management practices. The Carbon footprint was calculated by using the collected emission factors from literature as default values for each input and operation used for the production of crops as per guideline of ISO (2006) and IPCC (2006). The GHG emissions in the crop fields are taken from the studies of Pathak and Aggarwal (2012). The yield of lentil was 0.90 t ha-1 with a CF of 406 kg CO2-equivalentst-1 of lentil. Direct and indirect GHG emissions singly contributed the half of CF accounting 52.54% of total CF. The contribution of fertilizer, irrigation, machinery and labor inputs to the overall carbon footprint were 23.16%, 15.97%, 1.26% and 7.06%, respectively. Among the fertilizers, nitrogenous fertilizer was dominant and singly contributed to 70% of fertilizer CF. However, for developing best management practices for climate change mitigation in crop production of Bangladesh, further studies of soil and regional specific CFs of lentil are needed. Progressive Agriculture 27 (2): 162-167, 2016